Physical modeling of microwave ablation zone clinical margin variance. Issue 4 (22nd March 2016) - Deshazer, Garron; Merck, Derek; Hagmann, Mark; Dupuy, Damian E.; Prakash, Punit
Abstract : Purpose: The objective of this study is to measure through simulation the impact of (1) heterogeneity of biophysical parameters in tumor vs healthy tissue, (2) applicator placement relative to the tumor, and (3) proximity to large blood vessels on microwave ablation (MWA) treatment effect area. This will help identify the biophysical properties that have the greatest impact on improving clinical modeling of MWA procedures. Methods: The authors' approach was to develop two‐compartment models with variable tissue properties and simulate MWA procedures performed in liver with Perseon Medical's 915 MHz short‐tip applicator. Input parameters for the dielectric and thermal properties considered in this study were based on measurements for healthy and malignant (primary or metastatic) liver tissue previously reported in the literature. Compartment 1 (C1) represented normal, fatty, or cirrhotic liver, and compartment 2 (C2) represented a primary hepatocellular carcinoma tumor sample embedded within C1. To evaluate the sensitivity to tissue parameters, a range of clinically relevant tissue properties were simulated. To evaluate the impact of MWA antenna position, the authors simulated various tumor perfusion models with the antenna shifted 5 mm anteriorly and posteriorly. To evaluate the effect of local vasculature, the authors simulated an additional heat sink of various diameters and distances from the tumor. Dice coefficient statistics were used to evaluate ablation zone effects from these local heat sinks. Results: Models showed less than 11% of volume variability (1 cm 3 increase) in ablation treatment effect region when accounting for the difference in relative permittivity and electrical conductivity between malignant and healthy liver tissue. There was a 27% increase in volume when simulating thermal conductivity of fatty liver disease versus the baseline simulation. The ablation zone volume increased more than 36% when simulating cirrhotic surrounding liver tissue. Antenna placement relative to the tumor had minimal sensitivity to the absolute size of the treatment effect area, with less than 1.5 mm variation. However, when considering the overlap between the ablation zone and the ideal clinical margin when the antenna was displaced 5 mm anteriorly and posteriorly, there was approximately a 6 mm difference in the margins. Dice coefficient statistics showed as much as an 11% decrease in the ablation margin due to the presence of vessel heat sinks within the model. Conclusions: The results from simulating the variance in malignant tissue thermal and electrical properties will help guide better approximations for MWA treatments. The results suggest that assuming malignant and healthy liver tissues have similar dielectric properties is a reasonable first approximation. Antenna placement relative to the tumor has minimal impact on the absolute size of the ablation zone, yet it does cause relevant variation between desired treatment margin and ablation zone. Blood vessel cooling, especially hepatic vessels close to the region of interest, may be a significant factor to consider in treatment planning. Further data need to be collected for assessing treatment planning utility of modeling MWA in this context.